2021
DOI: 10.2334/josnusd.20-0648
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation in the trigeminal spinal subnucleus interpolaris/caudalis modulates orofacial incisional mechanical pain hypersensitivity associated with orofacial injury in infancy

Abstract: Infantile tissue injury induces sensory deficits in adulthood. Infantile facial incision (IFI) was reported to cause an enhancement of incision-induced mechanical hypersensitivity in adulthood due to acceleration of the trigeminal ganglion neuronal excitability. However, the effects of IFI on activation of microglia in the spinal trigeminal nucleus and its involvement in facial pain sensitivity is not well known. Methods: A facial skin incision was made in the left whisker pad in infant (IFI) and/or adult rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…In contrast, in ltrated T cells in the spinal dorsal horn are reported to contribute to neuropathic pain in female animals 8,16 . In the Vc, we found that the prolonged incision-induced mechanical allodynia in male rats was dependent on microglia, which was consistent with a previous report 4 . Although CD3-positive cells were seen in the Vc after whisker pad skin reincision in both sexes, the number of CD3-positive cells was very small, suggesting that in ltrated T cells in the Vc are unlikely to be involved in prolonged incision-induced mechanical allodynia in female rats.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, in ltrated T cells in the spinal dorsal horn are reported to contribute to neuropathic pain in female animals 8,16 . In the Vc, we found that the prolonged incision-induced mechanical allodynia in male rats was dependent on microglia, which was consistent with a previous report 4 . Although CD3-positive cells were seen in the Vc after whisker pad skin reincision in both sexes, the number of CD3-positive cells was very small, suggesting that in ltrated T cells in the Vc are unlikely to be involved in prolonged incision-induced mechanical allodynia in female rats.…”
Section: Discussionsupporting
confidence: 93%
“…All rats were acclimated to the testing environment for 5 days. The von Frey laments (4,6,8,10,15,26,30,40,50,60, and 80 g) were applied to the left whisker pad skin according to the method described previously 41 . Each lament was used in an ascending manner.…”
Section: Measurement Hwtmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, nociceptive stimulation of the hind paw 3 days after birth changes the gene profile in the spinal dorsal horn, which was maintained until adulthood 2 . Functional alterations in glial cells such as microglia in adulthood were also caused by tissue injury in infancy 3 , 4 . After re-incision in the hind paw of the adult rats that experienced neonatal injury in the hind paw, microglia release brain-derived neurotrophic factor (BDNF) which elicits long-term potentiation of C-fiber-mediated synaptic responses in the spinal dorsal horn, culminating in the maintenance of excessive neuronal activity 5 .…”
Section: Introductionmentioning
confidence: 99%